IMPOLITENESS STRATEGIES USED IN CODA MOVIE BY SIAN HEDER - Fatmawati, Fatmawati; Burhamzah, Muftihaturrahmah; Rosalia, Harnita (Journal of English Literature and Linguistic Studies, 2024)
This study aims to determine the types of impoliteness strategies and the factors that can influence impoliteness in the movie CODA. The data used is taken from the script of a movie titled CODA directed by Sian Heder (2021). The movie CODA is a musical drama that tells the dream of an ordinary girl from a deaf family. This study describes the variety of impoliteness found in the dialog of the characters in the movie. The analysis used a descriptive qualitative method to analyze the data. There are two data sources used, those are primary data and secondary data. This research used the theory of impoliteness from Culpeper (1996) to analyze the impoliteness data found in the film script. After conducting this research, the results show that there are five types of impoliteness strategies used by the characters in CODA, those are: bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock politeness and finally withhold politeness. As for the factors that influence the occurrence of impoliteness in this movie, it shows five factors, namely, power, anger, intimacy, intentionality, and social gap. Based on this study, we found 30 extracts consisting of 8 data for bald on record impoliteness, 10 data for positive impoliteness, 7 data for negative impoliteness, 3 data for the use of sarcasm or mock politeness, and 2 data for withhold politeness. As for the factors that influence impoliteness, it is divided into 8 factors of intentionality, 9 factors of anger, 9 factors of intimacy, 2 factors of power and finally the factor of social gap 2 times.